Premium Choice Steaks Purchased from Grocery Outlets Are Generally More Tender Throughout the Year than Lower Quality Grade Steaks - A. M. Collins; J. A. Unruh; T. A. Houser; S. Stroda (Kansas Agricultural Experiment Station Research Reports, 2016)
Consumers typically have the opportunity to select steaks from a variety of marketing categories that relate to quality, price, and expected tenderness. Research on quantifying characteristics of strip steaks from different marketing programs available in self-serve retail display cases and establishing benchmark data for strip steak comparisons for future years is needed. The purpose of this study was to determine mechanical tenderness as well as physical and cooking characteristics of strip steaks purchased from self-serve display cases in grocery store outlets throughout the year.
Keywords: tenderness; retail; seasonality